ACQUIRING ECONOMIC AND SOCIAL STABILITY IN CHEKHOV’S A MARRIAGE PROPOSAL - Irwan Sumarsono; Imam Dui Agusalim; Eny Kusumawati; Aliv Faizal Muhammad; Radina Anggun Nurisma (Undiksha Press, 2023)
A Marriage Proposal is one of Anton Chekhov’s famous short plays. It was written in 1889 and performed for the first time in 1890. In this play, Chekhov criticized the nineteenth-century Russian society especially the landowners or the wealthy classes who got married to a woman or a man from the same class in the society, driven not by their true love or affection, but by money to acquire economically and keep their social stability. This study analyzed how the characters of the play think and see the marriage institution. The study is qualitative research with a sociological approach. The approach was used to understand the work by comparing the content of the work with the society where the play was written using social sciences. Data were collected from the main source and the other sources before they were analyzed using the descriptive-analytic techniques A Marriage Proposal was the main source of this study, and the other sources were derived from books, journals, and the internet. Keywords: proposal, marriage, social stability, true love, affection